Innovative methods of evaluating the counterparty during the organization internal control - E. A. Kirova; T. V. Perminova (Вестник университета)
The article discusses the key issues of internal control measures when choosing a counterparty during the formation of an innovative economy. The purpose of the study is to develop indicators characterizing the counterparty, as well as an innovative risk matrix used when choosing a counterparty and allowing to identify risks and visually represent the characteristics of the counterparty. To achieve this goal of the article, the following tasks were solved: indicators of economic stability and information support used when choosing a counterparty were proposed; An innovative risk matrix and risk assessment criteria have been developed that allow the organization to objectively assess the counterparty and conclude contracts on the principles of economic validity, reliability and integrity, significantly reducing economic risks. As a result of the conducted research, innovative methods of assessing the counterparty are proposed, which provide an opportunity to obtain its objective characteristics before concluding a business agreement, as well as to rank tax risks. The article uses the methods of a systematic approach, analysis and synthesis, as well as the method of expert assessments.